COUNSELOR INTERPERSONAL COMMUNICATION STRATEGY IN AN EFFORTS TO OVERCOME DEPENDENCE AND IMPROVE THE SUCCESS OF DRUG ABUSE PATIENTS AT THE BHAYANGKARA MEDAN DRUG ABUSE PREVENTION REHABILITATION INSTITUTION - Ratih Dwi Indah R; Leylia Khairani; Rahmanita Ginting (RADJA PUBLIKA, 2024)
Drug abuse is a serious problem that affects the health and well-being of individuals. At the Bhayangkara Medan Drug Abuse Prevention Rehabilitation Institute, counselors' interpersonal communication strategies play an important role in the patient rehabilitation process. However, there have been few studies exploring the effectiveness of these strategies in overcoming addiction. This study aims to identify and analyze the interpersonal communication strategies used by counselors in overcoming addiction and increasing the success of drug abuse patient rehabilitation. How do the interpersonal communication strategies implemented by counselors affect the success of patient rehabilitation at the institution? Method This study used a qualitative approach with in-depth interview techniques with counselors and patients at the Bhayangkara Medan Drug Abuse Prevention Rehabilitation Institute. Data were analyzed thematically to identify patterns and relationships between communication strategies and rehabilitation outcomes. The results showed that counselors used communication strategies such as empathy, active listening, and building trusting relationships. These strategies have been shown to be effective in increasing patient engagement and reducing stigma, which in turn increases the success of rehabilitation. Appropriate interpersonal communication strategies are essential for the success of drug abuse patient rehabilitation. Further training is needed for counselors to improve their communication skills. In addition, institutions are also advised to conduct regular evaluations of the effectiveness of the communication strategies implemented.